Hepatocellular Carcinoma in a Large Canadian Urban Centre: Stage at Treatment and Its Potential Determinants - Korosh Khalili; Ravi Menezes; Leyla Kochak Yazdi; Hyun-Jung Jang; Tae Kyoung Kim; Suraj Sharma; Jordan Feld; Morris Sherman (Canadian Journal of Gastroenterology and Hepatology)
OBJECTIVE: To determine whether there is a significant difference in tumour stage between patients initially found with hepatocellular carcinoma (HCC) at a tertiary hepatobiliary centre and patients referred with tumours detected elsewhere; and to determine variables associated with referral in a palliative stage.